Formulation and In-vitro Evaluation of Mucoadhesive Buccal Patches of Cyproheptadine Hydrochloride - S. Himabindu, D. Sathish, Shayeda (Journal of Applied Pharmaceutical Science)
The goal of the present investigation was to design and evaluate mucoadhesive buccal patches of Cyproheptadine Hydrochloride (CPH) which is a sedating antihistamine with antimuscarinic, serotonin-antagonist, and calcium-channel blocking action. Buccal films were made with Hydroxy propylcellulose (HPC EF) and Hydroxy Propyl Methyl Cellulose (HPMC E15) as mucoadhesive polymers. Permeation of CPH was calculated ex vivo using porcine buccal membrane. The patches were evaluated for weight variation, thickness variation, surface pH, moisture absorption, in vitro residence time, mechanical properties, in vitro release, ex vivo permeation studies and drug content uniformity. The formulation F8 of HPMC E15 was found to give the better results and release of drug from the film followed Higuchi and Korsmeyer and Peppas models.
Keywords: Cyproheptadine Hydrochloride, ex vivo permeation, mucoadhesive, buccal patch, mechanical properties, diffusion.